Changes in Motor Function in a Child with Cerebral Palsy Following Multiple Botulinum Toxin Injections: A Case Report - Nancy Lennon; Chris Church; Jose J. Salazar-Torres; Faithe Kalisperis; Freeman Miller; Jason J. Howard (Children, 2025)
Objective: The objective of this study was to examine 7 years of clinical physical therapy measures in a child with spastic diplegic cerebral palsy (CP) who received multiple botulinum toxin type A (BoNT-A) injections. Methods: A boy diagnosed with spastic diplegic CP, Gross Motor Function Classification System level II, received four episodes of BoNT-A from ages 4 to 10 years. Serial clinical measures of muscle strength, spasticity, lower extremity passive range of motion, gait kinematics, and gross motor function were collected in the gait analysis lab from age 3 to 10 years. Results: After improvements from ages 3 to 7 years, gait and motor function declined from ages 8 to 10 years with no improvement in spasticity or range of motion measurements. Muscle testing and gait kinematics defined a loss of plantarflexion strength. Conclusions: A decline in gross motor skills and gait is not typical for a child with spastic diplegia at age 8 years and its association with BoNT-A injections needs to be considered. This case demonstrates the importance of evaluating treatment outcomes for youth with spastic CP utilizing a set of reliable, and clinically useful measures of strength, spasticity, contracture, gait, and motor function. Critical examination of impairment and functional level measures defines goals, guides treatment, and evaluates outcomes. With this approach, pediatric therapists can empower families to make well-informed decisions.